Microquasars as heating sources of the intergalactic medium during reionization of the Universe - Douna, Vanesa Mariel (2018)
The effect of the primeval sources of radiation and particles on the thermodynamical state of the intergalactic medium during the epoch of reionization is still unclear. In this work, we explore the contribution of electrons accelerated in the jets of high-redshift microquasars to heating and ionizing the intergalactic medium. We develop Monte Carlo simulations of the propagation and energy deposition of these electrons as they travel away from their sources. We find that microquasars contribute significantly to heating the intergalactic medium and are effective ionizers only near the galaxies. Their effect on heating is of the same order of magnitude as that of cosmic rays from supernovae.